A Rigorous Systematic Review of Probiotics for the Prevention of Antibiotic-Associated Diarrhea: Efficacy, Safety, Strain Specificity, and Risk Stratification in Adult and Populations - I Dewa Ayu Meyta Putri Sandradevi (The International Journal of Medical Science and Health Research, 2025)
Introduction Antibiotic-associated diarrhea (AAD) represents the most frequent gastrointestinal adverse event associated with antimicrobial therapy, affecting between 5% and 35% of patients depending on the drug and host factors.1 This adverse effect arises from antibiotic-induced gut microbiota dysbiosis, which compromises colonization resistance and favors the overgrowth of opportunistic pathogens, most severely Clostridium difficile.1 Probiotics—live microbial preparations—are hypothesized to restore intestinal microbiota balance, thereby preventing diarrhea.3 This systematic review and meta-analysis synthesizes the latest evidence from 42 adult and 24 randomized controlled trials (RCTs) to quantify the efficacy and safety profile of probiotics for AAD and Clostridium difficile-associated diarrhea (CDAD) prophylaxis. Methods A systematic literature search was conducted across PubMed, Google Scholar, Semantic Scholar, Springer, Wiley Online Library, targeting RCTs in adult and populations receiving antibiotics.4 Study selection and data extraction rigorously adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines.6 Pooled analyses were performed using a Random Effects Model to calculate the Risk Ratio (RR), Mean Difference (MD), and the Number Needed to Treat for an additional beneficial outcome (NNTB) across twelve primary and secondary outcomes.4 Results Probiotics demonstrated a statistically significant protective effect against AAD in the overall analysis for adults (RR 0.63, 95% CI 0.54 to 0.73, p<0.00001; NNT 20) and a stronger effect in (RR 0.45, 95% CI 0.36 to 0.56; NNTB 9).3 The protective effect against the severe outcome, CDAD, was highly significant (RR 0.40, 95% CI 0.30 to 0.52), particularly in trials enrolling participants with a baseline CDAD risk exceeding 5% (RR 0.30, NNTB 12).7 Subgroup analyses confirmed superior efficacy with specific strains (Lactobacillus rhamnosus GG and Saccharomyces boulardii) and a dose-response relationship, with high doses (≥5 billion CFUs/day) showing superior efficacy (RR 0.37 vs. RR 0.68 for low dose).3 Sensitivity analysis, excluding studies with high bias, showed the protective effect against AAD was no longer statistically significant in adults (RR 0.78, 95% CI 0.57 to 1.07, p=0.13).4 Overall adverse events were slightly reduced in the probiotic group (RR 0.83), and no serious adverse events were reported in the included RCT populations.3 Discussion The significant overall reduction in AAD incidence supports the prophylactic use of probiotics, but the critical sensitivity analysis reveals that this generalized benefit is highly susceptible to methodological bias in adult studies.4 Therefore, clinical recommendations must emphasize risk stratification, prioritizing prophylaxis for patients and high-risk adults (CDAD risk >5%), where the evidence remains robust and clinically meaningful (NNTB 9 and 12, respectively).3 The failure to reduce C. difficile detection rates suggests that the primary protective mechanism involves toxin neutralization and barrier function enhancement rather than pathogen eradication.7 Conclusion Probiotics are effective and generally safe agents for AAD prevention, with definitive utility in populations and for targeted CDAD prevention in high-risk groups. Future research must focus on high-quality, blinded RCTs to establish definitive efficacy and cost-effectiveness in low-risk adults.